New partial evaluation function in constructive hypher-heuristic framework for examination timetabling problem. - Pour, Sh. Mohammad; Md Sultan, Abu Bakar; Sulaiman, Md. Nasir; Zarrin, Bahram (Praise Worthy Prize, 2009)
In this paper we introduce a new partial evaluation function formula to evaluate partial solutions in a constructive hyperheuristic framework for solving Examination Timetabling Problem (ETTP). Since scheduling of each exam may restrict resources for remained unscheduled examinations, the function in order to evaluate partial solutions in each step, not only pays attention to situation of scheduled exams in current partial solution but also considers state of unscheduled exams after each scheduling. The function focuses on effect of previous scheduling of exams on time feasibility resource of remained unscheduled ones through a Bubble sort mechanism. The main formula is integrated by proportional coefficient. The framework applied on a graph based constructive hyperheuristic framework which its base is introduce in [1]. The efficiency of formula is analyzed and the prediction embedded in the new partial evaluation function is discussed.